2023
DOI: 10.1186/s40359-023-01078-6
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions, fear of progression and health-related quality of life during acute treatment and follow-up care in paediatric cancer patients and their parents: a cross-sectional study

Abstract: Background This study examines the role of illness perceptions and fear of progression (FoP) in paediatric cancer patients and their parents for patient’s health-related quality of life (HRQoL), controlling for sociodemographic and medical variables. 4–18-year-old patients in acute treatment or follow-up care and one parent were examined. Methods N = 46 patient-parent dyads in acute treatment and n = 84 dyads in follow-up care completed measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…found that several illness perceptions are significant predictors of HRQoL in 8‐12‐year‐old cancer patients, with the perception of negative consequences being the strongest predictor 29 . Also, our work group has recently contributed research on 4‐18‐year‐old cancer patients in acute treatment and in follow‐up care: Similar to results in adult cancer patients and survivors, and similar to Fonseca's results, we found that several illness perceptions contribute to the child's HRQoL, 30 namely the perception of symptoms and cyclicity of their illness. However, the aforementioned studies used cross‐sectional data, which limits the causal interpretation of results.…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…found that several illness perceptions are significant predictors of HRQoL in 8‐12‐year‐old cancer patients, with the perception of negative consequences being the strongest predictor 29 . Also, our work group has recently contributed research on 4‐18‐year‐old cancer patients in acute treatment and in follow‐up care: Similar to results in adult cancer patients and survivors, and similar to Fonseca's results, we found that several illness perceptions contribute to the child's HRQoL, 30 namely the perception of symptoms and cyclicity of their illness. However, the aforementioned studies used cross‐sectional data, which limits the causal interpretation of results.…”
Section: Introductionsupporting
confidence: 86%
“…Six‐month‐test‐retest‐reliability of the English original was good, with >0.5 for all scales (except timeline‐cyclical) in a sample of n = 76 adult patients with rheumatoid arthritis 46 . The puppet interview has been validated with n = 41 children in acute treatment and n = 34 children in follow‐up care and shows acceptable internal consistency for the dimensions timeline‐acute/chronic and personal control 44 . As the puppet interview is closely based on the IPQ‐R questionnaire, scores and items are comparable to each other.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations